2016
DOI: 10.1007/s10877-016-9963-0
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of the Ambu AuraGain versus the LMA supreme in patients undergoing gynaecologic laparoscopic surgery

Abstract: Second generation supraglottic airway devices providing high seal airway pressures are suitable for patients undergoing gynecologic laparoscopy. We compared the seal pressure achieved by the new Ambu AuraGain™ versus LMA Supreme™ following pneumoperitoneum in the Trendelenburg position. Sixty female patients were randomly allocated to ventilation with either the AuraGain or the Supreme. A target-controlled system was used to administer total intravenous anesthesia. Intracuff pressure was maintained below 60 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 18 publications
8
47
0
Order By: Relevance
“…However, our data are in line with those reported for the LMA Protector in previous studies . The OLP of the LMA Protector was comparable to or even higher than that described for the ProSeal and the Ambu AuraGain, and superior to that of the i‐gel and the LMA Supreme; this finding may be related to the cuff material and design of the LMA Protector .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, our data are in line with those reported for the LMA Protector in previous studies . The OLP of the LMA Protector was comparable to or even higher than that described for the ProSeal and the Ambu AuraGain, and superior to that of the i‐gel and the LMA Supreme; this finding may be related to the cuff material and design of the LMA Protector .…”
Section: Discussionsupporting
confidence: 92%
“…The overall success rate of the LMA Protector found in our present study (98%) is comparable to other second‐generation SADs such as the LMA ProSeal TM (91–100%), the LMA Supreme TM (92–100%) and the Ambu AuraGain (92–100%), but inferior to the Classic TM LMA (99.8–100%) . The learning curve with the LMA Protector is probably steeper than that of first‐generation SADs and similar to that of second‐generation SADs, which may justify the fact that 56% of our patients required manoeuvres to facilitate insertion .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In those studies, an OLP of 25 cmH 2 O was reached . Similar OLP's as in our study were found by Keller in the ProSeal™ laryngeal mask in obese patients and for the AuraGain™ in a study by Lopez et al in patients undergoing gynecologic surgery, as in a study by Moser et al No data on obese patients exist for the AuraGain™. Higher OLP's may be reached because of the better adaptation of the shape of the mask due to the fat deposits in the neck.…”
Section: Discussionsupporting
confidence: 91%
“…[9][10][11] Previous studies have reported conflicting results regarding differences in OLP between the Auragain and the Supreme. Lopez et al 10 compared the Auragain with the Supreme and showed a higher mean OLP of 34 cmH 2 O for the Auragain (vs 29 cmH 2 O in the Supreme). Nevertheless, other studies comparing the Auragain with the Supreme have reported no significant differences in OLP between the two devices.…”
Section: Résumémentioning
confidence: 99%